The Effect of Hermetia illucens Larvae on the Hematology of Tilapia (Oreochromis niloticus) Infected Edwardsiella tarda - Tirani, Elisabeth; Maftuch, Maftuch; Fadjar, Mohammad; Awaluddin, Muhammad (Department of Aquaculture, 2024)
Non-specific defense is the main defense in fish. One of the natural ingredients as a source immunostimulant isH. illucens larvae with a protein content of up to 30%. H. illucens larvae contains alkaloids, tannins, terpenoidsand saponins as immunostimulating agents. Immunostimulants are biological compounds that can boost theimmune system body. The purpose of this study is to find out the effect of H. illucens larvae in increasingimmunity non specific in tilapia (O. niloticus) which infected with E. tarda. In giving H. illucens larvae feed adlibitum with concentrations of A(30%), B(40%), C(50%), K(0%). In this research method, a completelyrandomized design (CRD) was used with 5 treatments and 3 replications in which each aquarium contained 10tilapia. Parameters tested are leukocytes, differential leukocytes, erythrocytes and hemoglobin. The resultsshowed that intake of 50% H. illucens larvae on tilapia could increase non-specific immunity, such as totalleukocytes, total erythrocytes, differential leukocytes, hemoglobin